Can The Sustainable Growth Rate (SGR) Moderate the Impact of ESG Risk Rating and Capital Structure on Firm Value? - Hasanah, Zahrotul; Rahmawati, Mia Ika (Politeknik Negeri Jember, 2025)
This research aims to find out the effect of Environmental, Social and Governance (ESG) risk rating and capital structure on the firm value which is moderated by Sustainable Growth rate (SGR). The research applies quantitatively. Furthermore, the data were secondary and in a form of annual reports and financial reports company listed on the ESG Leaders (IDXESGL) The Indonesia Stock Exchange from 2021 until 2023, it was taken from www.idx.co.id and GIBEI STIESIA, also ESG data of Risk Rating. Moreover, the data collection technique used saturated sampling with 90 data samples observed. This hypothesis testing uses multiple linear regression analysis using Moderated Regression Analysis (MRA). The result shows that ESG which is a proxy with risk rating has a negative and significant effect on the firm value. Capital structure which is a proxy with DER has a negative and significant effect on the firm value. Additionally, ESG risk rating which is moderated by sustainable growth rate has a negative and significant effect on the firm value. However, capital structure which is moderated by sustainable growth rate has a negative and insignificant effect on the firm value.